Toward Improving BIM Acceptance in FM: A Conceptual Model Integrating TTF and TAM (Journal of Engineering, 2023)
Substantial research has been performed on Building Information Modeling (BIM) in various topics, for instance, the use and benefit of BIM in design, construction, sustainable environment building, and Facility assets over the past several years. Although there are various studies on these topics, Building Information Modeling (BIM) awareness through facilities management is still relatively poor. The researcher's interest is increased in BIM study is based heavily upon the perception that it can facilitate the exchange and reuse of information during various project phases. This property and others can be used in the Iraqi Construction industry to motivate the government to eliminate the change resistance to use innovations in the Iraqi construction industry. Even though many scholars and practitioners agree on the potential application and benefits of BIM in construction/ Facilities Management FM, it is yet unknown why BIM is used and what criteria facilitate BIM achievement in O&M. As long as the actual usage and acceptance of BIM in the Operation and Maintenance phase is still a central issue in practice, therefor depending on the extensive well ground literature review a conceptual acceptance model is proposed in this paper by applying the technology acceptance theories such as Technology Acceptance Model (TAM) and Task Technology Fit (TTF) to explore how the extent of facilities management staff going to accept and adopt the new international technology (BIM).